The Effect of Sacrificial Agents in the Photodegradation of Methylene Blue Using Ag-Fe3O4 Nanoparticles - Frisellya Dirgantari; Nasikhudin; Herlin Pujiarti; Markus Diantoro (Universitas Negeri Surabaya, 2026)
Organic dyes in water are hazardous pollutants due to their toxic properties. One method capable of decomposing these pollutants is photocatalysis. Magnetite (Fe₃O₄) is an iron oxide that can be used as a photocatalyst material and synthesized using the coprecipitation method. These properties facilitate the separation of impurities from the medium. However, Fe₃O₄ has limited photocatalytic activity, so it needs to be composited with silver (Ag) to increase light absorption. Ag material can be produced using AgNO₃ as a source of silver ions. The resulting catalyst, with the addition of Sacrificial Agent solutions, was tested for photocatalytic Methylene Blue solution. The XRD, EDX, SEM, and Photocatalytic characterization results showed a crystalline Fe₃O₄ structure and appropriate material composition. This study demonstrates that adding Ag can enhance the photocatalytic activity of Fe₃O₄, while adding SA can minimize electron-hole recombination and increase the MB degradation efficiency.